Penegakan Hukum terhadap Perusakan dan Pencurian Sarana Bantu Navigasi Pelayaran (SBNP) di Wilayah Kerja Distrik Navigasi Tipe A Kelas I Belawan - Ahmad Ridho Arif (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This research examine law enforcement against the destruction and theft of aids to marine navigation. This research is a normative juridical study with an empirical approach, utilizing a descriptive-analytical method. The results show that Aids to Marine Navigation play an essential role in ensuring shipping safety and security. Although their existence are regulated by law, but problems such as destruction and theft of Aids to Marine Navigation are continue to occur. Law enforcement against the destruction and theft of Aids to Marine Navigation has not been effective. The influencing factors of law enforcement in the Navigation District Type A Class I Belawan include: (a) legal structure, (b) legal esubstance, and (c) legal culture.